Cognitive impairment in children with CACNA1A mutations. (21st May 2019) - Humbertclaude, Veronique; Riant, Florence; Krams, Benjamin; Zimmermann, Valerie; Nagot, Nicolas; Annequin, Daniel; Echenne, Bernard; Tournier‐Lasserve, Elisabeth; Roubertie, Agathe; ,
Abstract : Aim: To describe the clinico‐radiological phenotype of children with a CACNA1A mutation and to precisely evaluate their learning ability and cognitive status. Method: Children between the ages of 3 and 18 years harboring a pathogenic CACNA1A mutation associated with episodic ataxia, hemiplegic migraine, benign paroxysmal torticollis, benign paroxysmal vertigo, or benign paroxysmal tonic upgaze, were enrolled in this cross‐sectional study. Data concerning psychomotor development, academic performance, educational management, clinical examination at inclusion, and brain imaging were collected. Cognitive assessment was performed using age‐standardized scales. Results: Eighteen patients (nine males, nine females; mean age at inclusion: 11y 7mo [SD 4y 5mo; range 3y–17y 11mo]) from 14 families were enrolled. Eleven patients displayed the coexistence or consecutive occurrence of more than one type of episodic event. Nine patients exhibited abnormal neurological examination at inclusion. Brain magnetic resonance imaging (MRI) showed cerebellar atrophy in five patients. Psychomotor development was delayed in nine patients and academic difficulties were reported by the parents in 15 patients; nine patients were in special education. Impairment of intellectual function was assessed in six of the 12 patients with interpretable Full‐scale IQ scores and was more frequent when cerebellar atrophy was present on MRI. Interpretation: Cognitive impairment is commonly associated with CACNA1A mutations. We suggest that CACNA1A ‐associated phenotype should be considered a neurodevelopmental disorder. What this paper adds: Cognitive disabilities and academic difficulties are common in children with CACNA1A mutations associated with episodic syndromes. Cognitive function ranges from normal to moderate intellectual disorder in wheelchair‐dependent children. Patients with vermian atrophy are at a higher risk of cognitive impairment. What this paper adds: Cognitive disabilities and academic difficulties are common in children with CACNA1A mutations associated with episodic syndromes. Cognitive function ranges from normal to moderate intellectual disorder in wheelchair‐dependent children. Patients with vermian atrophy are at a higher risk of cognitive impairment.